Network disruption detected in CR (Costa Rica) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Costa Rica. Data sourced from IODA.
Network Disruption Incident ID: CR-2026-0001. Severity: critical. Confidence: 70%